Population analysis and the effects of Gaussian basis set quality and quantum mechanical approach: main group through heavy element species - North, Sasha C.; Jorgensen, Kameron R.; Pricetolstoy, Jason; Wilson, Angela K. (Frontiers in Chemistry, 2023)
Atomic charge was calculated using different population analysis methods including orbital-based methods (Mulliken, Löwdin, and Natural Population Analysis), volume-based methods (Atoms-in-Molecules (AIM) and Hirshfeld), and potential derived charges (CHELP, CHELPG, and Merz-Kollman). The impact of basis set and quantum mechanical method choices upon population analysis has been considered. The basis sets utilized include Pople (6-21G**, 6-31G**, 6-311G**) and Dunning (cc-pVnZ, aug-cc-pVnZ; n=D, T, Q, 5) basis sets, for main group molecules, Dunning basis sets for a transition-metal compound, vanadium oxide (VO), and the relativistic correlation-consistent (cc-pVnZ-DK3,cc-pwCVnZ-DK3 for Lr, and cc-pVnZ-DK for F, n=D,T,Q) basis sets for an actinide molecule, LrF. The quantum methods chosen include two density functional (PBE0 and B3LYP), Hartree-Fock, and second-order Møller-Plesset perturbation theory (MP2) approaches. The Hirshfeld approach is shown to have the greatest numerical stability (i.e., precision or non-variability) in the assignment of atomic charge with respect to basis set and level of theory.